The professional personnel of the Silliman University Library System, 1950-1966 a study - Bañas, Eliseo P.; Atienza, Daisy B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1974)
This study set out to accomplish the following: (1) to discover the initial personal characteristics that Silliman University Library personnel bring to their jobs; (2) to discover the initial academic characteristics of the same group; (3) to ascertain, through statistical approaches, the relationships between these initial characteristics and their overall performance while on the job; and, (4) to determine the relationships between the same initial characteristics and their length of service with the library system
Analysis of the data gathered has led to these findings. The model Silliman University librarian earned his first undergraduate degree at the age of 26, joined the library system when about 28 years old, at a time when he already had two dependents to look after. Furthermore, he came into the library system with a Bachelor of Science in Education degree, had earned 17 units of library science courses, but without any scholastic honors to his credit. Also, in overall performance he rates as above average and stays with the system for a period of seven and a half years. His personal and academic characteristics correlate poorly with his overall performance rating, and only moderately with his length of service with the system
This paper suggests further inquiries bearing on factors affecting initial salaries, rate of turnover, administrative organization, and predictive evaluative instruments
Typescript
Vita
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Silliman University Library